Lack of an association between SNPs within the cholinergic receptor genes and smoking behavior in a Czech post-MONICA study - Hubacek, Jaroslav A; Lanska, Vera; Adamkova, Vera (Genetics and molecular biology, 2014)
Smoking has a significant heritable component of approximately 30-60%. Recent genome wide association studies have identified single nucleotide polymorphisms (SNPs) within the nicotinic cholinergic receptor subunits 3 (rs578776), 5 (rs16969968) and β3 (rs6474412), which are associated with nicotine dependence in Western European populations. To analyze the association in a Czech population, we genotyped 1,191 males and 1,368 females (post-MONICA study). The WHO protocol was used to examine smoking status and the number of cigarettes smoked per day. There were 32.1% current and 27.6% past smokers among the males and 22.5% current and 13.8% past smokers among the females. We have not confirmed the original results: the SNPs rs16969968 (p = 0.07), rs578776 (p = 0.16) and rs6474412 (p = 0.76) were not associated with smoking status (never-smokers vs. ever-smokers) in the entire population, if a codominant model of analysis was used. This result was valid for both the male and female subpopulations if analyzed separately and adjusted for age. Finally, in ever-smokers, the number of cigarettes smoked per day was also independent of different genotypes, regardless of which polymorphism (and gender) was analyzed (the lowest p value was 0.49). The association between the cholinergic receptors-nicotinic subunits (-3, -5 and -ß3), and smoking behavior may be population-dependent.
Keywords: cholinergic receptors; polymorphism; smoking